Frequency of Helicobacter Pylori Infection in Patients with Dyspepsia - Iqbal, Aqsa; Zafar, Zainab; Rehman, Abdur (Indus Journal of Bioscience Research, 2025)
Background: Helicobacter pylori (H. pylori) is a gram-negative bacterium commonly associated with gastrointestinal disorders, including dyspepsia, peptic ulcers, and gastritis. Objective: This study aimed to determine the frequency of H. pylori infection in patients with dyspepsia and explore its relationship with demographic and clinical factors. Methods: A cross-sectional study was conducted at Unit I, Department of Medicine, Benazir Bhutto Hospital, Rawalpindi. A total of 150 dyspeptic patients, aged 20-70 years, were enrolled using non-probability consecutive sampling. Data were collected on demographic and clinical characteristics, including age, gender, BMI, hypertension, diabetes, smoking history, and family history of dyspepsia. Results: The study found a 45% prevalence of Helicobacter pylori infection in dyspeptic patients. The infection was more common in patients aged 40-60 years and those with a BMI ≥ 30 kg/m². The infection rate was significantly higher in patients with peptic ulcer disease (60%), while lower rates were observed in those with gastroesophageal reflux disease (38%) and other causes of dyspepsia (33%). There was no significant difference in H. pylori infection based on the duration of symptoms, with infection rates ranging from 42% to 48% across the 1-12, 13-24, and 25-36-month duration groups. The T-test analysis revealed a significant difference in BMI between H. pylori positive (27.2 ± 4.5 kg/m²) and negative (24.8 ± 3.9 kg/m²) groups (p = 0.002), but no significant differences were found in age (p = 0.08) or symptom duration (p = 0.12). Conclusion: It is concluded that H. pylori infection is prevalent in dyspeptic patients, with significant associations observed with age and BMI. These findings highlight the need for H. pylori screening in dyspeptic patients, particularly those with higher BMI and from lower socioeconomic backgrounds.